Ontologi dalam pembelajaran: studi tentang hubungan mahasiswa dan dosen di uin maulana malik ibrahim malang - Nabilah, Carina Nasywa (Maliki Interdisciplinary Journal, 2025)
This paper examines the role of ontological foundations in shaping the learning experience within Islamic higher education, focusing on UIN Maulana Malik Ibrahim Malang. It analyzes how ontological views affect the dynamics of student–lecturer interactions and contribute to the development of critical thinking, conceptual clarity, and spiritual awareness among students. Employing a philosophical lens and supported by data from student surveys, the research shows that ontology is regarded by students as both relevant and vital to their academic growth. The study finds that ontological approaches encourage thoughtful reflection, promote empathetic and transparent academic communication, and enhance the depth of learning. Furthermore, it underscores the need for teaching strategies that are both contextual and participatory to improve comprehension of ontological concepts. The integration of ontological insights into curriculum planning is shown to foster a comprehensive educational process that supports intellectual, emotional, and spiritual growth. In conclusion, this study advocates for a deeper philosophical grounding in Islamic education to support the formation of well-rounded individuals